Material-specific ptychographic imaging at 13.5 nm using a high-order harmonic source - Eschen, Wilhelm; Loetgering, Lars; Schuster, Vittoria; Klas, Robert; Kirsche, Alexander; Berthold, Lutz; Steinert, Michael; Pertsch, Thomas; Gross, Herbert; Krause, Michael; Limpert, Jens; Rothhardt, Jan (Optics InfoBase Conference Papers, 2022)
We present a high-harmonic driven ptychographic EUV microscope operating at a wavelength of 13.5 nm. Sub-20 nm resolution is demonstrated and the accurate amplitude and phase images are harnessed to identify multiple materials of an integrated circuit.
CRIS-Team Scopus Importer:2023-04-20